Implementasi Profile Matching untuk Mengukur Kualitas Website Sistem Informasi Desa Sidokerto Menggunakan Model McCall - Zahra Awalia Santosa; Muhammad Yoga Pratama Chusnani; Rani Purbaningtyas; Sholihah Ayu Wulandari (Department of Informatics, Universitas Diponegoro, 2024)
In the era of information technology development, the Sidokerto Village information system website is utilized to provide the latest information to the community regarding the development of the village. To ensure the quality of the Sidokerto Village information system website, it is necessary to conduct software testing. This aims to prevent errors and ensure that all features and functionality are running properly. This test uses the Profile Matching method which is adjusted to the indicators of the McCall model to test quality. The main focus is on the Product Operation aspect, which includes Correctness, Reliability, Usability, Integrity, and Efficiency. The test results showed that the quality of the website reached an average score of 4.5, which indicates very good criteria. However, some improvements to the system are still needed to improve the overall quality.